Effects of chrysotile co-exposure on BaP binding in normal human fibroblasts. - Chang, M J (1983)
The effects of chrysotile and benzo(a)pyrene (BaP) co-exposure on uptake, metabolism and BaP binding to nucleic acids were investigated in normal human fibroblasts. A significant enhancement in these parameters was found when co-exposure was carried out under serum-free conditions. In the presence of serum, only a slight enhancement of BaP uptake was detected, while metabolism and binding to nucleic acids were not affected over the 8-hr incubation period studied.